PENGARUH KEPEMILIKAN MANAJERIAL DAN EARNING PER SHARE TERHADAP DIVIDEND PAYOUT RATIO PADA PERUSAHAAN MANUFAKTUR YANG LISTING DI BURSA EFEK INDONESIA - Muhammad Yusuf; Wa Ode Siti Rahmawati (Universitas Muhammadiyah Kendari, 2016)
This research is performed to examine the influence of Insider Ownership and Earning Per Share toward Dividend Payout Ratio in Manufacture Company that is listing in Indonesian Stock Exchange over period 2007 – 2010. The population of this research as much 9 company. Technique as used in interpretation of sample is census method (saturation sample). The analysis of technique as used is multiple linear regression and hypothesis testing by use of F (simultaneous) test and t (partial) test. The conclusion in this research indicate that simultanously of Insider Ownership and Earning Per Share is significant influential toward Dividend Payout Ratio. Partially of Insider Ownership variable is significant and positive influential toward Dividend Payout Ratio. And the partially of Earning Per Share variable is significant and negative influential toward Dividend Payout Ratio.